The effect of Giberelin on seed germination of Lokananta Varieties in Vitro - Syahfitri, Harahap (Jurnal Online Pertanian Tropik, 2020)
Lokananta varieties are one of the best vegetables in Indonesia. The aim of this research is to find out the influence of Giberlin on the formation of red onion buds for superfruit in vitro. The research was carried out in the Laboratory and Garden Experiments of Panca Budi Development University, Medan, which began in March until January 2019. The research was using a non-factorial Complete Design (RAL) non-factorial analysis, which was analyzed using the analysis of the data obtained, with the analysis of the data obtained. germination (%), number of leaves (cm), number of roots (fruit). and root length (cm) have no effect.   References Ariani, E., F.Y. Wicaksono, A.W. Irwan, T. Nurmala, and Y. Yuwariah. 2015. Pengaruh berbagai pengaturan jarak tanam dan konsentrasi giberelin (GA3) terhadap pertumbuhan dan hasil tanaman gandum (Triticum aestivum L.) kultivar dewata di dataran medium Jatinangor. Agric. Sci. J., 2(1):31–52. Badan Pusat Statistik. 2014. Produksi Bawang Merah Sumatera Utara. Biro Statistik Sumatera Utara, Medan. Elfianis, R, S. Hartina, I. Permanasari dan J. Handoko. Pengaruh Skarifikasi dan Hormaon Giberelin (GA3) Terhadap Daya Kecambah dan Pertumbuhan Bibit Palem Putri (Veitchia meerilli). Harahap, F. 2011. Kultur Jaringan Tanaman. Penerbit Unimed, Medan. Heddy, S. 1986. Hormon Tumbuhan. CV Rajawali. Jakarta. Iriani Enndang. 2013. Prospek Pengenbangan Inovasi Teknologi Bawang Merah di Lahan Sub Optimal (Lahan Pasir) Dalam Upaya Peningkatan Pendapatan Petani. Balai Pengkajian Teknologi (BPTP) Jawa Tengah. Lakitan, B. 1996. Fisiologi Pertumbuhan dan Perkembangan Tanaman. PT Raja Grafindo Persada. Jakarta. Luta, D.A., Siregar, M., Sabrina, T. and Harahap, F.S., 2020. Peran Aplikasi Pembenah Tanah Terhadap Sifat Kimia Tanah Pada Tanaman Bawang Merah. Jurnal Tanah dan Sumberdaya Lahan, 7(1), pp.121-125. Pavlista, A.D., K. Santra, and D.D. Baltensperger. 2013. Bioassay of winter wheat for gibberellic acid sensitivity. Am. J. of Plant Sci., 4:2015-2022. Salisbury, F.B. dan C.W. Ross. 1995. Fisiologi Tumbuhan. Biokimia Tumbuhan, Jilid 2. Penerjemah: Lukman D.R dan Sumaryono. Penerbit ITB. Bandung. Sari, H. P., C. Hanum, dan Charlog. 2014. Daya Kecambah dan Pertumbuhan Mucuna bracteata Melalui Pematahan Dormansi dan Pemberian Zat Pengatur Tumbuh Giberelin (Ga3). Jurnal Online Agroekoteknologi, 2 (2) : 630- 644. Surajudin As’ad., R. Yusuf, dan H. Mas’ud. 2015. Respon Tanaman Bawang Merah (Allium Ascalonicum L.) Varietas Lembah Palu Terhadap Pemberian Jenis Mulsa Dan Pupuk Organik Cair. Wattimena. 1988. Zat Pengatur Tumbuh Tanaman. PAU Bioteknologi IPB. Bogor.